On low frequency conducted EMI: interference mitigation with focus on the DC switching harmonic in the time and frequency domains - Pena Quintal, Angel Eduardo (2023)
The recent increase of interconnected electrical systems such as power supplies and communication links are creating problems associated with electromagnetic fields generated at different voltage levels and frequencies. Semiconductor switches used in for example Switched Mode Power Supplies are constantly increasing in power rating and frequency limits. In addition, wired communication links are also increasing the working bandwidth and channel capability to transfer more information in less time.